PERTANGGUNGJAWABAN PIDANA PENANGGUNG JAWAB KEGIATAN MENYAMPAIKAN PENDAPAT DI MUKA UMUM MENURUT UNDANG-UNDANG NOMOR 9 TAHUN 1998 TENTANG KEMERDEKAAN MENYAMPAIKAN PENDAPAT DI MUKA UMUM - Luki Jemi Hendrik (Legal Spirit, 2022)
Freedom of expression is the right of every individual that has been guaranteed by the constitution. Freedom of opinion has been regulated in Law Number 9 of 1998 concerning Freedom to Express Opinions in Public. In every activity of expressing opinions in public, there is a party in charge who is responsible from the beginning of the activity to the completion of the activity. This activity is not solely held without permission from the police, so the person in charge of the activity must prepare the conditions for obtaining permission from the police in carrying out the activity of conveying the opinion. Activities that already have a permit, usually there are anarchic actions carried out by members of the activity. So that in this paper it is necessary to know the factors that cause the person in charge of the activity not to fulfill the obligations and procedures for expressing opinions in public and if there are actions outside the procedure for expressing opinions, the legal responsibility of the person in charge of the activity is not continued in the legal process by law enforcers. in order not to cause turmoil in the community.